CAR, OER dan Inflasi sebagai Prediktor Profitabilitas - Ni Luh Putu Sri Purnama Pradnyani (JEMAP, 2020)
This research wanted to determine the effect of CAR, OER, and inflation on profitability. The sample in this study was State-Owned Commercial Banks (BUMN) listed on the Indonesia Stock Exchange (BEI) in 2015-2018. The sampling method used was purposive sampling with a sample of 4 banking sector companies that met the criteria in the study. The multiple linear regression was used as data analysis technique. Based on the research results, the t value was 2.877 with sig 0.014, which means that the CAR variable has a positive and significant effect on profitability. The results of OER research show the t value of -2.684 with sig 0.020, which means that OER has a negative and significant effect on profitability. The results of the inflation study show the t value of 2.334 with sig 0.037, which means that inflation has a positive and significant effect on profitability.